Pro-life or pro-abortion – Women's attitude toward abortion in Darjeeling, India - Pallabi Dasgupta; Romy Biswas; Dilip Kumar Das; Jayanta Kumar Roy (Archives of Medicine and Health Sciences, 2019)
Background and Objective: Despite liberal abortion law in India, majority of abortions are unsafe. Behavioral theory suggests that women's attitudes may influence their abortion decisions. The present study was conducted to find out women's attitude toward abortion and its predictors. Materials and Methods: A community-based cross-sectional study was conducted in Naxalbari block of Darjeeling district, West Bengal, India, among 420 women aged 15–49 years using a predesigned, pretested interview schedule. The women's attitude regarding abortion practices was determined based on Likert's three-point scale. Two-stage cluster analysis was used to classify the overall attitude of women. Binary logistic regression was used for finding out predictors of abortion attitude. Results: More than half (53.5%) of the women had an overall pro-life attitude and 46.5% women had an overall pro-abortion attitude. Women who were less educated with <5 years' schooling, unaware of legality of abortion, and never aborted had significantly higher odds of having overall pro-life attitude. Majority women viewed abortion as a sin (81.4%); 62.1% of women disagreed with abortion as a method of family planning; 87.4% disagreed with sex selection before abortion; and 57.4% women agreed on women's right to decide for abortion. Conclusion: Women's attitude of abortion depicted complex personal and moral choices marred with social stigma within which abortion decisions are made. For developing a pro-choice outlook, life skills education for women, creating supportive family environment, sensitizing young men through extensive awareness campaigns, and advocacy through health-care providers are needed.